Bringing state capacity into the debate: a key for energy transition in emerging economy - Winanti, Poppy Sulistyaning; Mas'udi, Wawan (Oxford University Press, 2022)
As energy consumption increases, adopting an energy transition policy has significantly intensified. The existing literature mainly argues that energy transition’s success entails ‘energy democracy’, which integrates social justice and economic equity with renewable transitions. Even though energy democracy has its merit in ensuring the energy transition, it ignores state capacity, especially in emerging economies where the state actors play a vital role in managing resources. By bringing state capacity into the discussion, this article offers a more comprehensive theoretical and empirical contribution to the current debate on energy transition in emerging economies like Indonesia. A country characterized by fragmented actors and competing interests in every arena of policies and level of governance. Therefore, in emerging economies, energy transition requires a ‘socio-technical capacity’ and ‘community engagement’—as proposed by energy-democracy theory—and the rigorous state’s capacity to make the transitions possible.